Fibre characteristics and follicle activity in Angora kids as affected by diet - O. Olivieri; M. Antonini; G. Acuti; M. Trabalza Marinucci (Italian Journal of Animal Science, 2011)
Factors that influence fibre growth in speciality fibre producing animals are not completely understood; however, this knowledge is important to develop practical and profitable production systems. The effects of nutrition on fibre growth and production in Angora goats have not been researched to the same degree as in sheep. Nutrition improvements generally result in increases in fleece weight and fibre diameter (Shahjalal et al., 1992; Galbraith, 1995)...